2015
DOI: 10.1364/oe.23.001567
|View full text |Cite
|
Sign up to set email alerts
|

High directional backlight using an integrated light guide plate

Abstract: A high directional backlight system that combined a composite microstructure light guide plate (LGP) with a collimated light source was proposed for eco-displays. The collimated planar light was expanded from a point light source and guided towards the normal direction by utilizing the micro-prism array on LGP. High uniformity of spatial luminous, 91%, with a narrow viewing cone of ± 4° can be achieved without additional optical films. Moreover, compared to the conventional backlight, only 5% of power consumpt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(10 citation statements)
references
References 12 publications
0
9
1
Order By: Relevance
“…To widen the viewing angle of an LCD, compensation films together with a directional backlight and a weak diffusive film can be employed . In our simulation, we used the compensation scheme proposed by Ge et al .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…To widen the viewing angle of an LCD, compensation films together with a directional backlight and a weak diffusive film can be employed . In our simulation, we used the compensation scheme proposed by Ge et al .…”
Section: Resultsmentioning
confidence: 99%
“…18 To widen the viewing angle of an LCD, compensation films together with a directional backlight and a weak diffusive film can be employed. 19,20 In our simulation, we used the compensation scheme proposed by Ge et al 21 The phase retardation from the LC layer is partially compensated by a negative C-plate, and the residual phase retardation is compensated by a biaxial film. The parameters of the negative C-plate and biaxial plate are as follows: n e, C = 1.5902, n o,C = 1.5866, n x,B = 1.5028, n y,B = 1.5000, n z, B = 1.5018, d C = 21.4 μm, and d B = 74.0 μm.…”
Section: Voltage-dependent Transmittancementioning
confidence: 99%
“…In consequence, the conventional LED conspicuous automotive light typically causes glare to night drivers, which elevates the danger of traffic. In order to solve the above problems, several new design ideas for car signal lights have been proposed [6][7][8][9]. For example, the indirect light installed with a micro-prism sheet and LED [1][2][3][4][5][6], which is more promising and has been used to construct an automotive rear light with an attractive pattern, as shown in Figure 1b, not only providing a smooth lighting surface, flexibility of shape, but also reducing the amount of LEDs used [10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, diffractive optical components offer an alternative approach for light extraction from the LGP at uniform intensity and viewing angle. Among numerous different grating geometries, which have been employed by various authors to attain uniform extraction, submicron diffraction gratings have been identified as the most promising technique [3]- [5].…”
Section: Introductionmentioning
confidence: 99%